Sideritis carpetana (Labiatae), a new high-mountain Mediterranean species from the marble outcrops of the Sierra de Guadarrama (Central System, Madrid, Segovia, Spain) - Jose Luis Izquierdo; Rosina Magaña Ugarte; Alba Gutiérrez-Girón; Concepción Obón de Castro; Diego Rivera Núñez; Rosario G. Gavilán (PhytoKeys)
A new species of Sideritis (Sideritis carpetana) is described from the calcareous, high-mountain Spanish flora in the central part of the Iberian Peninsula. It is found in a Mediterranean climate at high-elevation, perennial, calcareous grasslands, as well as in marble screes of anthropogenic origin in the Sierra de Guadarrama, Central System (Spain), in a reserve area within the Sierra de Guadarrama National Park, at 1996 m asl. Taxonomic morphological measurements were performed on collected specimens from Sierra de Guadarrama as well as on geographically-adjacent Sideritis (i.e., S. glacialis, S. pungens, S. hyssopifolia). The relationships among them were then explored with multivariate analysis. Sideritis carpetana is a dwarf shrub with an erect or decumbent habit, growing up to 15 cm; non-woody twigs with long hairs of 3–4 cells, leaves are entire, linear-oblanceolate, sparsely covered with trichomes; inflorescence is spiciform or slightly verticillated, flowers are yellow and nutlets ovoid. A key is supplied to help distinguish it from other high-mountain Iberian species included in section Sideritis. The species is unique in its combination of morphological and autoecological characters. S. carpetana shares similarities with S. glacialis, a species from Sierra Nevada, and its northern Mediterranean variant, S. glacialis subsp. fontqueriana from Sierra de Gúdar. They share morphological characters that are absent in other high-mountain Sideritis, reinforcing their Mediterranean character, as opposed to a more temperate or submediterranean character, such as those of the hyssopifolia group.